Pengaruh Brand Awareness dan Social Media Marketing Terhadap Minat Beli pada Es Teh Indonesia di Jakarta - Dania Nadhira; Donant Alananto Iskandar (UNIVERSITAS KALBIS, 2022)
This articel talks about the influence of brand awareness and social media marketing on buying interest in es teh indonesia, Jakarta. There are three variables in this study, namely brand awareness, social media marketing as the independent variable and purchase intention as the dependent variable. Then the object of this research is Es Teh Indonesia. This research is a quantitative research using google form as a tool to distribute questionnaires and SPSS 22 as a tool to calculate data with a sample of 150 respondents who are domiciled in DKI Jakarta, using non- probability sampling and purposive sampling techniques. The results of this study indicate that brand awareness and social media marketing affects buying interest in Es Teh Indonesia.